Simulation study of the effects on rectangular microstrip patch antenna loaded with materials of high permittivity - Mhd Iswandi, Bin Katutu. (Universiti Malaysia Sarawak (UNIMAS), 2004)
This research work is about the simulation study of the effects of rectangular microstrip patch antenna loaded with materials of high permittivity. This research work involves applying software from the equations using Matlab Software and simulation using Microwave Office 2002 Software. Various number of relative permittivity s, - from 3 to 16 to be used. Besides relative permittvity sr, there are several dimensions involved which comprising frequency of operation, thickness of substrate and tangent loss. Matlab Software was used to produce effects on antenna size and Microwave Office 2002 Software was used to produce effects on antenna performance using Smith Chart, VSWR,. Return Loss or S11 Magnitude and impedance Chart with different of relative permittivity sr. From this research work we may know the effects loading materials on rectangular microstrip patch antenna on its size and performance and on microstrip line size. This research work can be concluded with the loss of antenna performance could be improved by varying the substrate thickness.